Soybean molasses to replace corn for feedlot lambs on growth performance, carcass characteristics, and meat quality - Arruda, Maria Carolina G. [UNESP] (2021)
Soybean molasses (SBM) is a byproduct of the manufacture of soy protein concentrate and has high energy value. This byproduct has a high potential for use in the nutrition of ruminant animals, mainly in the replacement of other energy feeds such as corn grain. The objective of this study was to evaluate the inclusion of SBM to replace corn grain up to 30% dry matter (DM) in the total diet on growth performance, feeding behavior, carcass characteristics, and meat quality of feedlot lambs (1/2 Santa Ines x 1/2 Dorper). Forty intact male lambs with an initial average body weight of 20.6 +/- 2.5 kg and approximate age of 120 d were used. The animals were distributed in four treatments (0%, 10%, 20%, and 30% SBM), divided into five randomized blocks according to the initial weight and adapted for 16 d, with diets containing increasing concentrations of concentrate and SBM. Feeding behavior was analyzed at the beginning, middle, and final of the finishing period, and when animals reached 42 d on the finishing diet they were slaughtered. Data were evaluated using SAS software (version 9.4), by polynomial orthogonal contrasts, where the growth performance, carcass characteristics, and meat quality values were analyzed as randomized blocks, and the feeding behavior data as randomized blocks with a repeated measure over time. Significant differences were detected for the contrast 0 vs. SBM treatments, which the inclusion of SBM caused an increase (P <= 0.05) in ash intake but decreased the ether extract intake. The intake of DM in % body weight was higher for SBM treatments than 0% treatment (P <= 0.05). Feeding behavior, ruminating while lying down and drinking water presented a decreasing linear effect (P <= 0.05), and for feeding, efficiency increased with the addition of SBM (P <= 0.05). Fatty acids C14:0, C17:0, C17:1, C18:2n6c, C20:2, and C20:3n6 showed lower values with the inclusion of SBM (P = 0.05), while fatty acids C22:0 and C22:6n3 increased. The values of n6 polyunsaturated fatty acids and n-6/n-3 ratio were lower (P <= 0.05) for SBM treatments. The values of total polyunsaturated fatty acids showed a decreasing linear effect (P <= 0.05) with the inclusion of SBM. The use of up to 30% SBM in DM did not impair animal growth performance and feeding behavior did not cause damages to carcass parameters and still made the meat healthier, improving the n-6/n-3 ratio, therefore can be used to feed finishing lambs.